Penilaian keterancaman terhadap bencana bagi Pulau Makalehi, Sulawesi Utara, Indonesia - Cornelia Marschiavelli, Mone Iye; Niendyawati, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
Makalehi Island is one of Indonesia’s outer islands which plays an important role as a national borderline.Since vulnerability assessment as well as hazard and capacity assessment for small islands are needed to help in the decision making process of disaster management, this paper describes the vulnerability and capacity of Makalehi Island . It also proposes some alternatives for integrated vulnerability assessment for small islands in general and for Makalehi in particular. The methodology involves a survey conducted in early 2007 to gather primary data pertaining to soil, marine resources, and demography. The analysis used in this study is qualitative descriptive. Results illustrate both the vulnerability and capacity of Makalehi Island which can be used as an input in Indonesian small island management and development. The Makalehi depicts vulnerability to environmental, economic and social disasters. Yet it does also possess certain capacities that may be enhanced to further mitigate the impacts of disasters should they befall the island. A mitigation alternative that may be explored is the Integrated Coastal Zone Management (ICZM)